Set up multiplication/division of ratios to cancel out units you don't need for the final answer and introduce those that you do.
We have m/s and we want m/min so
(100m/s)(60s/min)=6000m/min
D. 1/4
Explanation:
a perfect square is written in the form
(1)
In our problem, we have this perfect square:
(2)
with C being unknown. However, by comparing (1) and (2), we know that
![2a=-1](https://tex.z-dn.net/?f=2a%3D-1)
So, we find
![a=-\frac{1}{2}](https://tex.z-dn.net/?f=a%3D-%5Cfrac%7B1%7D%7B2%7D)
and therefore, the missing term must be
![a^2 = \frac{1}{4}](https://tex.z-dn.net/?f=a%5E2%20%3D%20%5Cfrac%7B1%7D%7B4%7D)
so the complete square is
![x^2 -x +\frac{1}{4}](https://tex.z-dn.net/?f=x%5E2%20-x%20%2B%5Cfrac%7B1%7D%7B4%7D)
Answer:
2x
Step-by-step explanation:
10x/5 is the same as 1/5 times 10x.
Simplify to get 2x
(a)
![\displaystyle\int_3^\infty \frac{\mathrm dx}{x^2+9}=\lim_{b\to\infty}\int_{x=3}^{x=b}\frac{\mathrm dx}{x^2+9}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cint_3%5E%5Cinfty%20%5Cfrac%7B%5Cmathrm%20dx%7D%7Bx%5E2%2B9%7D%3D%5Clim_%7Bb%5Cto%5Cinfty%7D%5Cint_%7Bx%3D3%7D%5E%7Bx%3Db%7D%5Cfrac%7B%5Cmathrm%20dx%7D%7Bx%5E2%2B9%7D)
Substitute <em>x</em> = 3 tan(<em>t</em> ) and d<em>x</em> = 3 sec²(<em>t </em>) d<em>t</em> :
![\displaystyle\lim_{b\to\infty}\int_{t=\arctan(1)}^{t=\arctan\left(\frac b3\right)}\frac{3\sec^2(t)}{(3\tan(t))^2+9}\,\mathrm dt=\frac13\lim_{b\to\infty}\int_{t=\arctan(1)}^{t=\arctan\left(\frac b3\right)}\mathrm dt](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Clim_%7Bb%5Cto%5Cinfty%7D%5Cint_%7Bt%3D%5Carctan%281%29%7D%5E%7Bt%3D%5Carctan%5Cleft%28%5Cfrac%20b3%5Cright%29%7D%5Cfrac%7B3%5Csec%5E2%28t%29%7D%7B%283%5Ctan%28t%29%29%5E2%2B9%7D%5C%2C%5Cmathrm%20dt%3D%5Cfrac13%5Clim_%7Bb%5Cto%5Cinfty%7D%5Cint_%7Bt%3D%5Carctan%281%29%7D%5E%7Bt%3D%5Carctan%5Cleft%28%5Cfrac%20b3%5Cright%29%7D%5Cmathrm%20dt)
![=\displaystyle \frac13 \lim_{b\to\infty}\left(\arctan\left(\frac b3\right)-\arctan(1)\right)=\boxed{\dfrac\pi{12}}](https://tex.z-dn.net/?f=%3D%5Cdisplaystyle%20%5Cfrac13%20%5Clim_%7Bb%5Cto%5Cinfty%7D%5Cleft%28%5Carctan%5Cleft%28%5Cfrac%20b3%5Cright%29-%5Carctan%281%29%5Cright%29%3D%5Cboxed%7B%5Cdfrac%5Cpi%7B12%7D%7D)
(b) The series
![\displaystyle \sum_{n=3}^\infty \frac1{n^2+9}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Csum_%7Bn%3D3%7D%5E%5Cinfty%20%5Cfrac1%7Bn%5E2%2B9%7D)
converges by comparison to the convergent <em>p</em>-series,
![\displaystyle\sum_{n=3}^\infty\frac1{n^2}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Csum_%7Bn%3D3%7D%5E%5Cinfty%5Cfrac1%7Bn%5E2%7D)
(c) The series
![\displaystyle \sum_{n=1}^\infty \frac{(-1)^n (n^2+9)}{e^n}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Csum_%7Bn%3D1%7D%5E%5Cinfty%20%5Cfrac%7B%28-1%29%5En%20%28n%5E2%2B9%29%7D%7Be%5En%7D)
converges absolutely, since
![\displaystyle \sum_{n=1}^\infty \left|\frac{(-1)^n (n^2+9)}{e^n}\right|=\sum_{n=1}^\infty \frac{n^2+9}{e^n} < \sum_{n=1}^\infty \frac{n^2}{e^n} < \sum_{n=1}^\infty \frac1{e^n}=\frac1{e-1}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Csum_%7Bn%3D1%7D%5E%5Cinfty%20%5Cleft%7C%5Cfrac%7B%28-1%29%5En%20%28n%5E2%2B9%29%7D%7Be%5En%7D%5Cright%7C%3D%5Csum_%7Bn%3D1%7D%5E%5Cinfty%20%5Cfrac%7Bn%5E2%2B9%7D%7Be%5En%7D%20%3C%20%5Csum_%7Bn%3D1%7D%5E%5Cinfty%20%5Cfrac%7Bn%5E2%7D%7Be%5En%7D%20%3C%20%5Csum_%7Bn%3D1%7D%5E%5Cinfty%20%5Cfrac1%7Be%5En%7D%3D%5Cfrac1%7Be-1%7D)
That is, ∑ (-1)ⁿ (<em>n</em> ² + 9)/<em>e</em>ⁿ converges absolutely because ∑ |(-1)ⁿ (<em>n</em> ² + 9)/<em>e</em>ⁿ| = ∑ (<em>n</em> ² + 9)/<em>e</em>ⁿ in turn converges by comparison to a geometric series.